Question of Hungary. Report of the Special Political Committee. Seventeenth Session, 1200th Plenary Meeting - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly A draft resolution is submitted by the United States in which a request is made to the Secretary General for him to take any initiative he deems helpful in relation to the Hungarian question. The United States representative draws attention to the fact that the forces of time should not be allowed to mute the indignation of people who care for freedom. The draft resolution was adopted by 50 to 13 votes with 43 abstentions.